Dynamical erosion of asteroid groups in the region of the Pallas family - Carruba, V. [UNESP]; Machuca, J. F. [UNESP]; Gasparino, H. P. [UNESP] (Wiley-Blackwell, 2011)
In a previous paper, the current state of knowledge on the region of the Pallas dynamical family was revised. Here the dynamical evolution and possible origin of dynamical groups in the region are investigated. First, we study the case of asteroids at high eccentricity (e > 0.31). These objects are unstable because of encounters with Mars on time-scales of up to 340 Myr. Local background asteroids are currently the major source of high-eccentricity objects, but Barcelona family members will become the dominant source in about 250 Myr.Next, attention is focused on the lack of chaotic dynamics near the nu(6) secular resonance border in the region. Contrary to the case of the Phocaea family region, very limited chaotic behaviour was observed for real and fictitious particles in the central main belt near the nu(6) resonance. Using analytical and numerical tools, we find that the limited amplitude of the inclination region near the nu(6) resonance in the Pallas family region for which close encounters with Mars are possible explains the lack of chaotic behaviour found in a previous paper by Carruba.Finally, we investigate the long-term stability of the minor families and clumps identified in the previous paper, when non-gravitational effects are considered. We find that none of the minor clumps obtained by Carruba is currently interacting with non-linear secular resonances in the region. The classical clumps around (40134) 1998 QO53, (75938) 2000 CO80, (33969) 2000 NM13, (208080) 1999 VV180 and (70280) 1999 RA111 have large detectability times and could be considered reasonable candidates for groups originating from collisional events. We confirm the presence of the (4203) Brucato family observable in the space of proper frequencies (n, g, g + s) that has the largest detectability time of all groups in the region.
Keywords: celestial mechanics; minor planets, asteroids: general